On Some Neologisms Created by Stanisław Lem: An Etymological Study - Fastyn, Marcin (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article considers etymologies proposed in the Polish-Russian Dictionary of Stanisław Lem’s Neologisms (Polsko-rosyjski słownik Lemowych neologizmów) by Monika Krajewska. In the case of 28 lexical units (out of a total of 1,450), the study proposes a new etymology, correcting an obvious mistake or revealing new possibilities. This shows how difficult Lem’s language can be not only for average readers, but also for translators and linguists.